2018
DOI: 10.2478/anre-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

The impact of maternal age on foetal growth patterns and newborn size

Abstract: The association patterns between maternal age and foetal growth parameters as well as newborn size were analysed using a dataset of 4737 singleton term births taking place at the Viennese Danube hospital. Foetal growth patterns were reconstructed by the results of three ultrasound examinations carried out at the 11th/12th, 20th/21th and 32th/33thweek of gestation. In detail, crown-rump length, biparietal diameter, fronto-occipital diameter, head circumference, abdominal transverse diameter, abdominal anterior-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Bubble plot for meta-regression of LBW against year of the study births occurred at home (Klemm et al 2015). LBW is also associated with maternal age (Kirchweger et al 2018), BMI and height: young women (<20 years old) are 2.3 times more likely to give birth to infants with LBW compared to their older counterparts; underweight women (BMI<18.5 kg/m 2 ) are 2.43 fold more likely to have a LBW baby compared to mothers with BMI >18.5 kg/ m 2 ; and short-statured mothers (<152 cm) have increased LBW risk compared to women >160 cm (Britto et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Bubble plot for meta-regression of LBW against year of the study births occurred at home (Klemm et al 2015). LBW is also associated with maternal age (Kirchweger et al 2018), BMI and height: young women (<20 years old) are 2.3 times more likely to give birth to infants with LBW compared to their older counterparts; underweight women (BMI<18.5 kg/m 2 ) are 2.43 fold more likely to have a LBW baby compared to mothers with BMI >18.5 kg/ m 2 ; and short-statured mothers (<152 cm) have increased LBW risk compared to women >160 cm (Britto et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Instead the values of the 18-35-and over 35-year-olds are similarly low as the values of the adolescent mothers under 18 years of age. This seems surprising because adolescent mothers tend to have smaller and lighter children because their bodies are not fully developed yet and competition for nutrients leads to smaller offspring compared to adult women (Kirchweger et al 2018). We then compared the newborn parameters of the smoking group and those of the non-smoking group within each age category.…”
Section: Discussionmentioning
confidence: 99%
“…This ob-servation is in accordance with those of several previous studies, which showed that maternal obesity but also maternal short stature are risk factors for C-sections Hartmann 2007, 2017). Maternal somatic parameters however, are also significantly associated with fetal growth patterns and newborn size (Albouy-Ilaty et al 2011, Ay et al 2009, Dietz etal al 2009, Kirchweger et al 2018, Pölzlberger et al 2017. The effect of maternal age on fetal growth and newborn size however, is not a linear one, but a u-shaped on.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of maternal age on fetal growth and newborn size however, is not a linear one, but a u-shaped on. According to Kirchweger et al (2018), largest dimensions of fetuses and newborns are found among mothers ageing between 20 and 35 years, while younger mothers and older mothers showed smaller newborns and fetuses. Therefore, the positive association between maternal age and C-section rates and instrumental delivery rates cannot be explained by a positive association between maternal age and fetal growth.…”
Section: Discussionmentioning
confidence: 99%